1993
DOI: 10.1111/j.1745-459x.1993.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homogenization and Fat Content on Oral Perception of Low and High Viscosity Model Creams

Abstract: Assessed under low‐intensity red illumination, homogenized and thickened higher fat milk samples evoked higher sensory ratings of creaminess than did the unhomogenized or lower‐fat milks that had not been thickened to the viscosity of double cream. Furthermore, perceptual ratings of fat content showed the same dependency on homogenization, higher fat and thickness and were entirely accounted for by the creaminess ratings. This indicates that assessors recognize the type of milk or cream most similar to a rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…As reported in earlier studies, creaminess relates both to the textural properties viscosity and smoothness (Guinard & Mazzucchelli, 1996;Kokini & Cussler, 1983;Richardson et al, 1993) but in some product categories it may also depend on flavour (Kilcast & Clegg, 2002;RichardsonHarman et al, 2000). However, no direct information about flavour can be extracted from images, explaining why in the case of yoghurt Creaminess cannot be well predicted from image analysis.…”
Section: Yoghurtmentioning
confidence: 86%
See 1 more Smart Citation
“…As reported in earlier studies, creaminess relates both to the textural properties viscosity and smoothness (Guinard & Mazzucchelli, 1996;Kokini & Cussler, 1983;Richardson et al, 1993) but in some product categories it may also depend on flavour (Kilcast & Clegg, 2002;RichardsonHarman et al, 2000). However, no direct information about flavour can be extracted from images, explaining why in the case of yoghurt Creaminess cannot be well predicted from image analysis.…”
Section: Yoghurtmentioning
confidence: 86%
“…Consumers seem to consider a product creamy when it has a high fat content, has dairy flavour and a viscous, slippery, greasy and mouth coating texture (Richardson-Harman et al, 2000). Several researchers have found that creaminess relates both to thickness (depending on physical viscosity) and smoothness (depending on physical frictional forces) (Guinard & Mazzucchelli, 1996;Kokini & Cussler, 1983;Richardson, Booth, & Stanley, 1993). Other studies have found that creaminess is highly correlated to perceived fattiness in different dairy product categories (Frøst, Dijksterhuis, & Martens, 2001;Hyvö nen, Linna, Tuorila, & Dijksterhuis, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…However those proposals cannot account for the emergence of smoothness in dairy cream under specific microstructural and rheological conditions. When an emulsion with sufficiently high oil fraction and the natural dairy aroma and taste (from lactose and NaCl) is homogenised and then thickened using shear-thinning cellulose gum, a substantial rise in ratings of smoothness is seen (Richardson, Booth and Stanley 1993). One possibility is that the cream is squeezed to a monolayer of oil droplets between the tip of the tongue and the palate.…”
Section: Second Example: Dairy Emulsion Physicsmentioning
confidence: 99%
“…the distribution of fat globule sizes in dairy cream Richardson, Booth & Stanley, 1993;cp. Booth, 2005).…”
mentioning
confidence: 99%